An Integrative Framework of Stress, Attention, and Visuomotor Performance - Vine, Samuel J.; Moore, Lee J.; Wilson, Mark R. (Frontiers in Psychology, 2016)
The aim of this article is to present an integrative conceptual framework that depicts the effect of acute stress on the performance of visually guided motor skills. We draw upon seminal theories highlighting the importance of subjective interpretations of stress on subsequent performance and outline how models of disrupted attentional control might explain this effect through impairments in visuomotor control. We first synthesize and critically discuss empirical support for theories examining these relationships in isolation. We then outline our integrative framework that seeks to provide a more complete picture of the interacting influences of stress responses (challenge and threat) and attention in explaining how elevated stress may lead to different visuomotor performance outcomes. We propose a number of mechanisms that explain why evaluations of stress are related to attentional control, and highlight the emotion of anxiety as the most likely candidate to explain why negative reactions to stress lead to disrupted attention and poor visuomotor skill performance. Finally, we propose a number of feedback loops that explain why stress responses are often self-perpetuating, as well as a number of proposed interventions that are designed to help improve or maintain performance in real world performance environments (e.g., sport, surgery, military, and aviation).